Validation of the UV-Vis Spectrophotometric Method for the Determination of Ascorbic Acid Content in Beverage Preparations Based on a Standard Vitamin C Calibration Curve - Andaririt, Devita Riafinola; Purnaningtyas, Sri Rahayu Dwi; Wijayanto, Arif (Open Access Health Scientific Journal, 2025)
Background: Vitamin C or ascorbic acid (C₆H₈O₆) is an essential water-soluble compound, widely used in functional beverages due to its antioxidant properties. This compound plays a role in neutralizing free radicals, strengthening the immune system, and helping the absorption of iron in the body. Packaged beverages containing vitamin C can experience degradation due to storage temperature (pH), production process, and the length of product circulation on the market. This impacts degradation of ascorbic acid and decreases the levels of vitamin C in beverage preparations, so accurate and validated analytical methods are needed to ensure the conformity of ascorbic acid levels with the label.Methods: Determination of ascorbic acid levels using a UV-Vis spectrophotometer at maximum wavelength. A standard curve was prepared from a standard vitamin C solution with a concentration of 10–18 ppm, resulting in a regression equation as the basis for calculating sample levels. Method validation included linearity, accuracy, precision, limit of detection (LOD), and limit of quantitation (LOQ) tests according to quantitative analysis guidelines.Results: The standard curve equation is Y = 0.020x + 0.030Y with r2 = 0.995r indicating good linearity. The vitamin C content in the sample is 1.045 mg/140 mL or 103.5% of the label (1000 mg), still within the Pharmacopoeia limits (90–110%). The LOD and LOQ values are 0.429 ppm and 1.3 ppm, respectively. The precision results show a %RSD of 0.1260% and an accuracy (% recovery) of 103.5%.Conclusion:The results showed that the UV-Vis spectrophotometry method had good linearity, accuracy, and precision. The vitamin C content in the product met standards. Validation parameters demonstrated that this method was consistent in analyzing vitamin C in beverage preparations.